A ChIP-seq defined genome-wide map of vitamin D receptor binding: Associations with disease and evolution - Ramagopalan, Sreeram V.; Heger, Andreas; Berlanga, Antonio J.; Maugeri, Narelle J.; Lincoln, Matthew R.; Burrell, Amy; Handunnetthi, Lahiru; Handel, Adam E.; Disanto, Giulio; Orton, Sarah-Michelle; Watson, Corey T.; Morahan, Julia M.; et al. (Genome Research, 2010)
Initially thought to play a restricted role in calcium homeostasis, the pleiotropic actions of vitamin D in biology and their clinical significance are only now becoming apparent. However, the mode of action of vitamin D, through its cognate nuclear vitamin D receptor (VDR), and its contribution to diverse disorders, remain poorly understood. We determined VDR binding throughout the human genome using chromatin immunoprecipitation followed by massively parallel DNA sequencing (ChIP-seq). After calcitriol stimulation, we identified 2776 genomic positions occupied by the VDR and 229 genes with significant changes in expression in response to vitamin D. VDR binding sites were significantly enriched near autoimmune and cancer associated genes identified from genome-wide association (GWA) studies. Notable genes with VDR binding included IRF8, associated with MS, and PTPN2 associated with Crohn's disease and T1D. Furthermore, a number of single nucleotide polymorphism associations from GWA were located directly within VDR binding intervals, for example, rs13385731 associated with SLE and rs947474 associated with T1D. We also observed significant enrichment of VDR intervals within regions of positive selection among individuals of Asian and European descent. ChIP-seq determination of transcription factor binding, in combination with GWA data, provides a powerful approach to further understanding the molecular bases of complex diseases.
10.1101/gr.107920.110